2022
DOI: 10.3390/ijms23115883
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Endothelial P2Y Receptors in Cardiovascular Health: From Vascular Physiology to Pathology

Abstract: The endothelium plays a key role in blood vessel health. At the interface of the blood, it releases several mediators that regulate local processes that protect against the development of cardiovascular disease. In this interplay, there is increasing evidence for a role of extracellular nucleotides and endothelial purinergic P2Y receptors (P2Y-R) in vascular protection. Recent advances have revealed that endothelial P2Y1-R and P2Y2-R mediate nitric oxide-dependent vasorelaxation as well as endothelial cell pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 142 publications
0
6
0
Order By: Relevance
“…For this purpose, experiments with the NO probe DAR4M-AM in fluorescence microscopy were performed. In these experiments, to simulate the physiological release of NO, we treated endothelial cells with the purinergic agonist adenosine triphosphate (ATP), proven to act as an autocrine/paracrine mediator of the flow-induced NO release [ 32 ]. In these experiments, we set four experimental conditions: BAE-1 cells in control conditions (CTRL); cells treated with 100 µM of ATP for 5 min (ATP); cells treated with 1 µM of IPA for 30 min (IPA, Figure 4 a,b) and 24 h (IPA, Figure 4 c,d); and cells treated for 30 min ( Figure 4 a,b) or 24 h ( Figure 4 c,d) with IPA plus ATP in the last 5 min (IPA + ATP).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, experiments with the NO probe DAR4M-AM in fluorescence microscopy were performed. In these experiments, to simulate the physiological release of NO, we treated endothelial cells with the purinergic agonist adenosine triphosphate (ATP), proven to act as an autocrine/paracrine mediator of the flow-induced NO release [ 32 ]. In these experiments, we set four experimental conditions: BAE-1 cells in control conditions (CTRL); cells treated with 100 µM of ATP for 5 min (ATP); cells treated with 1 µM of IPA for 30 min (IPA, Figure 4 a,b) and 24 h (IPA, Figure 4 c,d); and cells treated for 30 min ( Figure 4 a,b) or 24 h ( Figure 4 c,d) with IPA plus ATP in the last 5 min (IPA + ATP).…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the mechanism involved in the IPA-dependent inhibition of NO release in BAE-1 cells stimulated by ATP, we performed a Western blot analysis of the Ser1179-phosphorylation level of endothelial nitric oxide synthase. It is indeed established that extracellular ATP binds to endothelial P2Y2 receptors, starting an intracellular cascade leading to Ser1179 eNOS phosphorylation (and consequent activation) [ 32 ]. For these experiments, the experimental conditions were the same as those described for Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the fact that the P2Y 1 receptor antagonist MRS2500 blocked the diastolic vasodepressor responses (i.e., systemic vasodilatation) and the systolic vasopressor responses (i.e., cardiac left ventricular contractility) induced by ADPβS [this study] clearly suggests that P2Y 1 receptors are involved in cardiovascular regulation. In keeping with this suggestion, other studies have recently revealed that endothelial P2Y 1 receptors are critical in mediating nitric oxide-dependent vasorelaxation [44] and in processes essential for the regeneration of damaged endothelium [45]. This knowledge has stimulated increased interest in considering the P2Y 1 receptor as a potential therapeutic target in the treatment of hypertension [46].…”
Section: Perspectives and Potential Clinical Significancementioning
confidence: 85%
“…P2Y receptor (P2YR), as a GPCR subfamily of eight subunits (P2YR1, 2, 4, 6, 11–14) known, can respond to extracellular nucleotides ( Cabou and Martinez, 2022 ). Among them, P2YR1, 11–13 are activated by ATP/ADP, P2YR4, 6, 14 are activated by UTP/UDP, and P2YR2 receptors are activated by ATP/UTP ( Abbracchio et al, 2006 ; Koles et al, 2019 ).…”
Section: Roles Of Class a G Protein-coupled Receptors In Cochleamentioning
confidence: 99%